BCG treatment for bladder cancer, from past to present use. Issue 3 (26th December 2014) - Alcorn, Jason; Burton, Rob; Topping, Annie
ABSTRACT Since the turn of the 20th century Bacillus Calmette‐Guerin (BCG) treatment for non‐muscle invasive bladder cancer (NMIBC) has been in and out of favour. However, only a small proportion of patients, as low as 16%, complete what is seen as a gold standard treatment. To understand why it is the gold standard treatment the epidemiology and aetiology of NMIBC is presented. This article discusses how BCG was first discovered in cows to it being used as a treatment for NMIBC. The issues of side effects which can be from mild to severe and local to systemic, will be discussed. The impact of age in the tolerance of this treatment will be also be looked at. In conclusion, with BCG treatment being the preferred option for NMIBC, it also comes with significant side effects. It is these that should be of concern to the health care professional as they can be potentially life threatening.